Нові знахідки дзеркал скіфського і сарматського часу з Закубання - Дударев, С.Л.; Бережна, В.А.; Колкова, С.П. (Археологія і давня історія України, 2021)
В останні роки на території сільських районів,
прилеглих до м. Армавір (РФ), що історично є Закубанням (тобто, областю лівого берега р. Кубані)
було випадково виявлено низку бронзових дзеркал
скіфської та сарматської доби. Вони надійшли до
музеїв та музейних куточків деяких міст і станиць східної частини Краснодарського краю РФ або
були виявлені «на руках» у місцевого населення, з наступною фіксацією краєзнавцями. Завданням цієї
статті є публікація знахідок зазначеної категорії
матеріальної культури, презентованих невеликою,
але досить цікавою і виразною серією. Найраніші
знахідки з опублікованих (с. Успенське) відносяться
до VII—VI та VI ст. до н. е. і входять у групу дзеркал, поширених серед культур скіфського світу від
Північного Причорномор’я до Туви. Інші артефакти сумарно вміщуються у межі другої половини
IV — I ст. до н. е. та характеризують відповідну
категорію матеріальної культури пам’яток сарматського часу Середньої Кубані. Подані у публікації дзеркала доповнюють географію та характеристики знахідок дзеркал раннього залізного віку східної частини Закубання. In recent years, on the territory of rural areas adjacent
to the city of Armavir (Russian Federation), historically
representing the Zakubanye (Trans-Kuban) region (i. e.,
the area of the left bank of the Kuban River), the number
of bronze mirrors of Scythian and Sarmatian Ages have
been found by chance. They entered the museums and
museum corners of some cities and villages or were recorded
in the private collections with subsequent fixation
by local historians. The purpose of this paper is to publish
the finds of this category which form a small but quite interesting
and expressive series. The earliest of the presented
specimens are finds from the village Uspenskоe.
The first mirror from the Uspenskoe village (fig. 1: 1, 2)
can be attributed to section I, type I, option 1 (mirrors
with a central handle, round flat disc with a rim and segment
loop) after T. M. Kuznetsova, and can be dated to
the 7th—6th centuries BC. The second mirror from the village
Uspenskoe (fig. 1: 3, 4) belongs to the 3rd variant of
the indicated type, with a trapezoid loop. According to
T. M. Kuznetsova, most of these mirrors are dated to the
6th century BC. Mirror 1 (fig. 2: 3, 4) from stanitsa Chamlykskaya
can be considered to belong to type II, option 2
(according to I. I. Marchenko), which attributes the mirrors
of this option to the 3rd—2nd centuries BC. The findings
of modern Russian archaeologists make it possible to
confirm the total dating of mirrors with scallops, similar
to the published sample 2 from stanitsa Chamlykskaya
(fig. 2: 1, 2) as 3rd—1st centuries BC.
Mirrors 1, 3, 4 (fig. 2: 5, 6; 3: 3—6) from stanitsa Voznesenskaya
and mirror 3 from the village Uspenskoe (fig. 1:
5, 6), in our opinion, can be included to the number of copies
of type III, version 1 by I. I. Marchenko. The date of
the mirrors of this version, according to this author, is
the second half of the 4th—3rd centuries BC. Mirror 2 from
stanitsa Voznesenskaya (fig. 3: 1, 2) belongs to type I,
option 2 according to I. I. Marchenko. The archaeologist
dates the finds of type I option 2 to the second half of the
4th — 2nd centuries BC. The mirrors presented in the publication
complement the geography and characteristics of
the early Iron Age mirrors found in the eastern part of the
Trans-Kuban region.